Early results of low-velocity ballistic femoral shaft fractures. Issue 11 (November 2022) - Donahue, Jeffrey; Heimke, Isabella; Cho, Elizabeth; Furdock, Ryan; Vallier, Heather A.
Highlights: Femoral shaft fractures secondary to closed injuries from blunt trauma have similar rates of infection and secondary procedures compared with those arising from low energy gunshot wounds. Fractures due to gunshot wound are more likely to be associated with arterial injury or compartment syndrome. Nonunion may be more common following closed blunt femoral fracture when compared with ballistic injuries. Abstract: Introduction: Ballistic femur fractures are a common injury treated at United States civilian trauma centers. This study investigates the outcomes of these injuries by comparing the rates of infection, nonunion, secondary operations, and associated injuries from low-velocity gunshot (GSW) injuries with fractures sustained by blunt trauma. Methods: A retrospective cohort comparative study was performed at a Level 1 trauma center. 345 patients with closed blunt or GSW femoral shaft fractures over 10 years were included. All were treated with intramedullary nail fixation. Superficial and deep infection, vascular injury, compartment syndrome, nonunion, and secondary operations were identified. Results: 148 patients in the GSW group and 197 patients in the blunt trauma group had overall mean age 33.5 years and 80% were male. Deep infection rates were similar There were no nonunions in the GSW group, contrasted with 8 (4.4%) nonunions in the blunt trauma group ( p = 0.02). The rate of compartment syndrome was higher in the GSW group (6.1% vs 0, p < 0.001). Arterial injury occurred in 9% following GSW (vs 0, p < 0.001). Overall, secondary unplanned procedure rates were the same: 8.1% for both groups. Discussion: Ballistic femoral shaft fractures are often equated with open injuries; however, rates of infection and secondary operations closely mirror that of closed injuries resulting from blunt force trauma. Nonunions may be more common after blunt injury, and compartment syndrome and arterial injury are substantially more common following GSW, warranting careful clinical assessment. Level of evidence: Prognostic, level III.